Change of blood group from A2 to Ax in a child with congenital abnormalities. Issue 12 (December 1975) - Bird, G W; Roberts, K D; Wingham, J
Abstract : A blood group change from A2 to Ax is described in a boy who had Fallot's tetralogy, oesophageal atresia, and a tracheo-oesophageal fistula. The change of blood group created a transfusion problem. The unusual serology is discussed.